Increasing Science Learning Activities and Outcomes through Student Teams Achievement Divisions for Grade VI Students of SD N 03 Kwangsan - Winasari, Febby (Universitas Sebelas Maret, 2022)
This study aims to increase the activity and learning outcomes of science about the solar system through the STAD type cooperative learning model in class VI students at SDN 03 Kwangsan in 2021/2022. This research is a class action research (PTK). This study applies the STAD type cooperative learning model. This research was conducted in 2 cycles consisting of planning, action, observation, and reflection. The research subjects were 16 students in class VI at SDN 03 Kwangsan, consisting of 9 girls and 7 boys. Sources of data come from students, class VI teachers, and documents. Data collection techniques are test techniques, interviews, and observation. Data validity uses source triangulation techniques. Data analysis used is data reduction, data presentation, and verification. The results of this study indicate that: (1) complete science learning outcomes in the first cycle of students who have completed 64.5% of students who have not completed 35.8%, cycle II of students who have completed 87.5% of students who have not completed 12.5%, ( 2) student learning activities in cycle I 45.84% and in cycle II 83.34%. The conclusion of this study is that through the application of the STAD type cooperative learning model can increase science learning activities and outcomes.